Ubiquitin-specific protease 7 maintains c-Myc stability to support pancreatic cancer glycolysis and tumor growth - Jichun Gu; Xi Xiao; Caifeng Zou; Yishen Mao; Chen Jin; Deliang Fu; Rongkun Li; Hengchao Li (Journal of Translational Medicine)
Abstract Background The typical pathological feature of pancreatic ductal adenocarcinoma (PDAC) is a significant increase in stromal reaction, leading to a hypoxic and poorly vascularized tumor microenvironment. Tumor cells undergo metabolic reprogramming, such as the Warburg effect, yet the underlying mechanisms are not fully understood. Methods Interference and overexpression experiments were conducted to analyze the in vivo and in vitro effects of USP7 on the growth and glycolysis of tumor cells. Small-molecule inhibitors of USP7 and transgenic mouse models of PDAC were employed to assess the consequences of targeting USP7 in PDAC. The molecular mechanism underlying USP7-induced c-Myc stabilization was determined by RNA sequencing, co-IP and western blot analyses. Results USP7 is abnormally overexpressed in PDAC and predicts a poor prognosis. Hypoxia and extracellular matrix stiffness can induce USP7 expression in PDAC cells. Genetic silencing of USP7 inhibits the glycolytic phenotypes in PDAC cells, while its overexpression has the opposite effect, as demonstrated by glucose uptake, lactate production, and extracellular acidification rate. Importantly, USP7 promotes PDAC tumor growth in a glycolysis-dependent manner. The small-molecule inhibitor P5091 targeting USP7 effectively suppresses the Warburg effect and cell growth in PDAC. In a transgenic mouse model of PDAC, named KPC, P5091 effectively blocks tumor progression. Mechanistically, USP7 interacts with c-Myc, enhancing its stability and expression, which in turn upregulates expression of glycolysis-related genes. Conclusions This study sheds light on the molecular mechanisms underlying the Warburg effect in PDAC and unveils USP7 as a potential therapeutic target for improving PDAC treatment.